Renewable energy support through feed-in tariffs: A retrospective stakeholder analysis - Majid Hashemi; Glenn P. Jenkins; Frank Milne (Queen's University, Department of Economics, 2023)
This study develops a generalized evaluation framework that can be used to quantify the financial, economic, stakeholder, and environmental impacts of renewable energy support programs. The application of this framework is demonstrated by evaluating the Feed-In Tariff (FIT) program for solar distributed energy resources (DER) in Ontario, Canada. Our analysis reveals that Ontario's FIT program has successfully promoted the adoption of solar DER across communities. However, the program has caused inequitable societal outcomes through a crosssubsidization with a present value of 9 CAD billion, paid for by the electricity consumer base for the benefit of only the 0.06 percent of electricity consumers who could install solar systems. The cost imposed on the Canadian economy ranges from 2.86 to 5.37 CAD billion, depending on the discount rate applied. The sensitivity analysis results indicate that the burden of this program on the Canadian economy would have been reduced by 50 percent if the program had been delayed and implemented in 2016 instead of 2010 due to the declining trend in solar system investment costs. The lessons from this analysis provide insights for designing future environmental and emission reduction policies.
Keywords: H23; O13; Q42; Q48; 330; renewable energy subsidy; distributed energy resources; feed-in tariff; stakeholderanalysis; benefit-cost analysis; Ontario; Canada